Suprapubic Catheter Migration: A Review of a Rare Complication - Amr Elmoheen; Mahmoud Saqr; Waleed Salem; Khalid Bashir; Ayman Hagras (Case Reports in Urology)
Background. Suprapubic catheter migration to the vesicoureteral junction is an unusual complication, causing an obstruction that led to hydronephrosis and dilation of the pelvicalyceal system. Case presentation. A 30-year-old man with a suprapubic catheter (SPC) that was inserted one month before this current Emergency Department (ED) visit had severe left flank pain for 48 hours. The SPC was inserted in the context of urethral injury after falling astride. Point-of-Care Ultrasound (POCUS) showed a semifilled urinary bladder and moderate hydronephrosis on the left side. A computed tomography scan (CT scan) of the abdomen was performed and showed migration of the suprapubic catheter’s tip into the left vesicoureteral junction, causing ureteral obstruction dilation of the ipsilateral pelvicalyceal system. The suprapubic catheter was changed in the ED, causing relief of symptoms, and the patient was referred to the urology department for follow-up. It was uneventful on the follow-up from the SPC clinic. Conclusions. This case report describes a rare complication of migration of the suprapubic catheter to the vesicoureteral junction causing acute ureteral obstruction and hydronephrosis.